Serviço social e liderança sindical: a parceria entre a ação do assistente social e os trabalhadores usuários de álcool e outras drogas na CESP Companhia Energética de São Paulo S.A. - Souza, Alvandira Generosa de (2009)
The purpose of this dissertation is to analyze the proposed actuation of the Social Service in the Prevention and Treatment of Alchool and Other Drugs Program offered by CESP- Companhia Energética de São Paulo, in partnership with the Union Sindicato dos Eletricitários de São Paulo, in the year of 2006. The study takes, as its central point of reflection, the great structural and political changes experienced by the electrical sector in Brazil, specifically; in CESP. The rhetoric of the worker´s health quality programs has many social barriers, achieving its real impact in the health of the drug addicted workers. It is still a problem dealing with this demand within CESP, although it has been coming increasingly acceptable and natural. The Social Service acts with caution and ethics, avoiding prejudice and judgments either within the company's management setting as in the interpersonal and social relationships. The research was performed in the dependencies of CESP, in three of its sites: in the company's headquarters in São Paulo Capital, and in the hydroelectric plants of Paraibuna and Jaguari, both located in the Paraiba Valley. A questionnaire was applied as an instrument of research and, based on the results, we articulated the analysis among the context of the workers in the company, the gathered knowledge on the subject and the participation of the Union in the Prevention and Treatment of Alchool and Other Drugs Program. This research contributed to a better comprehension of problem´s extension in the company, that is, the increase of alcohol and other drugs utilization, and also to know how the employees, addicted or not, see the of the Social Service´s actuation. Contributed, as well, to develop a new coordinated plan, including new ways to lead and manage this and other programs to CESP´s employees